О существовании функций Ляпунова в задачах устойчивости интегральных множеств - Игнатьев, А.О. (Український математичний журнал, 1993)
A nonautonomous system of ordinary differential equations is considered. If this system admits a uniformly asymptotically stable integral set, then a neighborhood of this set contains a function similar to the Lyapunov function.